Expression characteristics and function of CAS and a new beta-amyrin synthase in triterpenoid synthesis in birch (Betula platyphylla Suk.). (May 2020) - Yin, Jing; Yang, Jie; Ma, Hongsi; Liang, Tian; Li, Ying; Xiao, Jialei; Tian, Hongmei; Xu, Zhiqiang; Zhan, Yaguang
Highlights: BpCAS and Bpβ-AS were preferentially expressed in roots and stems, respectively. BpCAS and Bpβ-AS were induced by MeJA, GA3, ABA, ethylene and mechanical damage. The inhibition of Bpβ-AS gene positively regulates synthesis of betulinic acid. The conversion of 2, 3-oxidosqualene to betulinic acid and oleanolic acid when BpCAS was interferenced. BpCAS and Bpβ-AS were involved in the growth and development of birch. Abstract: Triterpenoids produced by the secondary metabolism of Betula platyphylla Suk. exhibit important pharmacological activities, such as tumor inhibition, anti-HIV, and defense against pathogens, but the yield of natural synthesis is low, which is insufficient to meet people's needs. In this study, we identified two OSC genes of birch, named as BpCAS and Bpβ-AS, respectively. The expression of BpCAS and Bpβ-AS were higher levels in roots and in stems, respectively, and they induced expression in response to methyl jasmonate (MeJA), gibberellin (GA3), abscisic acid (ABA), ethylene and mechanical damage. The function of the two genes in the triterpene synthesis of birch was identified by reverse genetics. The inhibition of Bpβ-AS gene positively regulates synthesis of betulinic acid. BpCAS interference can significantly promote the upregulation of lupeol synthase gene (BPW) and β-amyrin synthase gene (BPY), and conversion of 2, 3-oxidosqualene to the downstream products betulinic acid and oleanolic acid. This study provided a basis for the genetic improvement of triterpenoid synthesis in birch through genetic engineering. The obtained transgenic birch and suspension cells served as material resources for birch triterpenoid applications in further.